Respuesta :
Answer:
Step1: Subtract (cx+d) from both sides of the given equation
Therefore the value of x in the given equation is [tex]x=\frac{a-d}{b+c}[/tex]
Step-by-step explanation:
Given equation is a-bx=cx+d
To solve the given equation for x :
a-bx=cx+d
Step1: Subtract (cx+d) from both sides of the given equation
a-bx-(cx+d)=cx+d-(cx+d)
a-bx-cx-d=cx+d-cx-d
a-bx-cx-d=0
Rewritting the above equation as below
a-b-bx-cx=0
(a-b)-x(b+c)=0 (here combining the like terms )
-x(b+c)=-(a-d)
Therefore the value of x in the given equation is [tex]x=\frac{a-d}{b+c}[/tex]